Croatia: The Long and Winding Road Towards Compliance With the EU State Aid Law - Žunić Kovačević, Nataša; Gadžo, Stjepan (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
This chapter examines the evolution of state aid and subsidy policies in Croatia against the backdrop of the European Union (EU) law. In doing so, it aims to contribute to the broader discussion on the convergence of state aid practices within the EU. It emphasises how the EU accession process impacted Croatia’s subsidy landscape. Three distinct stages in Croatian subsidy policies are identified: pre Stabilisation and Accession Agreement (SAA) era, the accession period marked by alignment with EU competition policy, and the post-accession stage where Croatia shares competence with the EU institutions. The chapter describes the challenges, legal reforms, and achievements of Croatia in aligning with the EU state aid law. On analysing Croatian policy and practice in the area of subsidies, it concludes that a remarkable degree of compliance with the EU law has been achieved. Conversely, there exists plenty of room for improvement from an economic perspective, given that Croatia still has an unfavourable state aid structure and a substantial total aid expenditure relative to its GDP. Keywords: subsidies, state aids, EU law, public finance law